Detection and quantification of pesticide residues in tomatoes sold in urban markets of Ouagadougou, Burkina Faso - Dione, Michel M.; Djouaka, R.; Mbokou, S.F.; Ilboudo, Guy S.; Ouedraogo, A.A.; Dinede, Getachew; Roesel, Kristina; Grace, Delia; Knight-Jones, Theodore J.D. (Frontiers Media, 2023)
Introduction: “What people worry about, and what makes them sick and kills them, are not the same” is maxim for risk communication experts. In Burkina Faso, pesticides are used by vegetable producers to improve productivity. However, consumer concern over pesticide use is high. Of course, if over-used pesticides could have serious health consequences for producers and consumers and also cause ecological damage.